ChemInform Abstract: Synthesis and Anticancer Activities of 5, 6, 7‐Trimethoxy‐N‐phenyl(ethyl)‐4‐aminoquinazoline Derivatives. Issue 52 (24th December 2013) - Zhang, Ying; Jin, Linhong; Xiang, Hongmei; Wu, Jian; Wang, Peiyi; Hu, Deyu; Xue, Wei; Yang, Song
Abstract The microwave‐assisted synthesis and the biological evaluation of a series of the title compounds is described.